Role of Inclusion “Smart City” Concept as a Factor in Improving the Socio-economic Performance of the Territory - Makushkin, Sergey A.; Kirillov, Andrey V.; Novikov, Vladimir S.; Shaizhanov, Mukhambet K.; Seidina, Moldir Z. (International Journal of Economics and Financial Issues, 2016)
The theoretical foundation of the concept of “social quality” as a research methodology of complex processes of social development of territories and communities. Analyzes key elements of the “social quality”, the problem of their relationship, and priority in the study. Traditional indicators of the level of socio-economic systems, such as, for example, gross domestic product, the volume of industrial production, the volume of investment in fixed assets, the volume of agricultural production, and the like are not accurate and that very importantly, sufficient criteria to assess the welfare of the country or its individual regions. But these factors are now becoming more and more important. One of the urgent problems of the modern Russian society is the uneven development of the territories. Due to differences in the initial conditions and characteristics of federal and regional policy in the space of modern Russia is implementing a wide range of changes. Geographically, the heterogeneity of the Russian society takes on a variety of forms: the parameters of the development of megacities-cities, provinces and rural areas differ not only in economic terms, but also demographically, culturally and so forth. Keywords: economic growth; social quality; stratification JEL Classifications: A13, Q34; Z13